Assessment of Burnout and its Related Factors in the Faculty Members and Medical Staff of Neyshabur University of Medical Sciences, Iran, in 2022 - Hassan Ebrahimpour-Sadagheyani; Farin Tatari (Iranian Journal of Nursing and Midwifery Research)
Background: Faculty members and medical staff are prone to burnout syndrome. Burnout has harmful consequences for the organization, society, and individual life. Therefore, this study was conducted to determine burnout and its related factors among faculty members and medical staff at Neyshabur University of Medical Sciences, Iran. Materials and Methods: This cross-sectional study was conducted on 410 medical faculty members and medical staff at Neyshabur University of Medical Sciences in 2022. Stratified sampling was conducted. Data were collected using the Maslach Burnout Inventory and interpreted using the t-test, Pearson correlation coefficient, and one-way ANOVA at a significance level of α = 0.05. Results: The total burnout score of medical staff and faculty members was 53.78 (15.43) and 50.85 (13.18) out of 135, respectively, with no significant difference between them (p = 0.192). The majority of faculty members had moderate Emotional Exhaustion (EE) (46.64%), high depersonalization (DP) (71.67%), and low Personal Accomplishment (PA) (56.67%), while the majority of medical staff had high EE (49.71%), high DP (60.0%), and low PA. The workload factor in medical staff and faculty members, which had the highest score, showed a direct and significant relationship with the burnout score. The communication factor among medical staff and faculty members had an inverse and significant relationship with the burnout score. Conclusions: Faculty members and medical staff experienced an average level of burnout, which is worth considering. According to the results, university administrators should take appropriate actions to reduce burnout.